EKSEKUSI âAb INTESTATOâ WARISAN DUA BANDING SATU: RASIONALISASI SURAH ANNISA AYAT 11 - Rasyid, Idris (Jurusan Syariah dan Ekonomi Islam Institut Agama Islam Negeri (IAIN) Parepare, 2016)
In Inheritance laws, principle is applicable. If someone dies, then all rights and obligations switch to the heirs. This principle is stated in a French proverb